1439Hepatitis B prevalence in the Indian Subcontinent: a systematic review and meta-analysis. (2nd September 2021) - Hogan, Sam; McBride, Kate; Page, Andrew; Dixit, Sameer
Abstract: Background: Hepatitis B virus (HBV) infections are a major global health burden. Although a vaccine exists for HBV, some developing nations still struggle to reduce prevalence. While the countries within the Indian Subcontinent have vaccination programs, HBV prevalence varies. It is important to identify population groups at risk. Methods: Several databases were systematically searched for papers appropriate studies. Studies were included if the sample population lived within one of the selected countries and had no other existing health issues. The studies were assessed for risk of bias, and pooled estimates were created. Subgroups which were assessed included countries, sex, rural and urban populations. Results: The pooled prevalence of all studies (N = 56) was 4%. For the countries with multiple included studies, the prevalence for India, Pakistan, Bangladesh and Nepal were calculated as 3%, 6%, 5% and 1% respectively. Most of the studies were assessed as being of reasonable quality. There was a chance that publication bias was present. Conclusions: While some of the populations had the expected prevalence for the country in which the study was set, other subpopulations had higher prevalence. The highest HBV prevalence was found in displaced persons and those engaging in risk taking behaviours, however some high prevalence groups did not have a clear reason. Key messages: Although HBV prevalence in general is lower at present than in the past, there are still at-risk groups with higher prevalence than the general population.